Plataforma digital “Trilha do Conhecimento”: o uso de tecnologias de informação e comunicação para criação e aplicação de objetos educacionais no ensino de biologia - Jeronimo Agostinho Freire (2019)
Developed from the perspective of mobile learning, the present study proposed the description and analysis of the use of information and communication technologies in the teaching-learning process, through the creation and application of educational objects, about Biology, for mobile devices, like smartphones. In this context, the present study proposed to develop educational objects within the scope of information and communication technologies, and to analyze their application in the teaching-learning process of contents of the discipline of Biology. The population of the present study consisted of students who were in the second and third years of high school in a public state school in the city of Belo Horizonte / Minas Gerais, in the years 2018 and 2019. The number of participants varied at each stage of the study, respecting the willingness of students to participate. In the first stage was created an online digital platform called "Knowledge Trail", which allowed the creation of three editable educational objects: two track games and a “crossings simulator”, based on the reading of fast response codes, QR code, for smartphone. For the two track games, the content Nervous System and Population Genetics were explored and the “crossings simulator” was directed only to the teaching of Population Genetics, as it is a particularly challenging. In the second stage, an applicability test of the use of both the digital platform and the educational objects was performed with high school students. For this, were applied in classes of 2nd year, a trail game about the Nervous System, and, in classes of 3rd year, the crossing simulator about Population Genetics. In the next step, two questionnaires were applied to verify the viability of using the smartphone, to know the profile, as well as the students' conception regarding the use of the developed technologies. During the fourth stage, two educational objects were applied to students of the third year of high school, as a complementary didactic strategy in teaching Population Genetics content: “crossing simulator” and “Board Game”. Finally, in the fifth stage, we analyzed the results of the students in the process of evaluation of the content Population Genetics, carried out through the game "Track on the Board". As results of this study we have the creation of the platform "Knowledge Trail" and the educational objects described. The applicability test revealed the viability of use of the information and communication technologies developed for the teaching of Biology and directed methodological adjustments to the application stage. The data obtained through the questionnaires revealed that 95.9% of the students have a smartphone, 95.1% of the participants considered the participation during the application of the educational objects as pleasurable and that 97.6% considered that the participation in these games contributed in some way form for your learning. In the groups in which the trail game and the crossings simulator were applied, the yield in relation to the percentage of individual and global hits on Population Genetics was considered good, but new quantitative and qualitative studies should be performed to evaluate the performance in the teaching-learning process with the use of digital educational objects developed in this study. It is hoped that the results of this study can contribute to the debate on the insertion of digital technologies in education as a way to improve learning, especially in the teaching of Biology contents, through the developed products: digital platform that enables that teachers in any field of knowledge create, edit and apply educational contents and use the educational objects “Track Games” and Crossing Simulator ”.